Effects of a trauma‐informed mindful recovery program on comorbid pain, anxiety, and substance use during primary care buprenorphine treatment: A proof‐of‐concept study. Issue 3 (5th December 2022) - Schuman‐Olivier, Zev; Fatkin, Thomas; Creedon, Timothy B.; Samawi, Farah; Moore, Sarah K.; Okst, Kayley; Fredericksen, Alaine (Kiera); Oxnard, Alexandra (Sasha); Roll, David; Smith, Lydia; Cook, Benjamin Lê; Weiss, Roger D.
Abstract: Background: A mindfulness‐based intervention that reduces comorbid pain, anxiety, and substance use during office‐based opioid treatment (OBOT) could enhance retention and prevent overdose. We conducted a pilot study of the Mindful Recovery OUD Care Continuum (M‐ROCC), a 24‐week trauma‐informed program with a motivationally‐sensitive curriculum. Methods: Patients prescribed buprenorphine ( N = 18) enrolled in M‐ROCC. We collected urine toxicology biweekly. At 0, 4, and 24 weeks, participants completed PROMIS‐Pain, PROMIS‐Anxiety, Mindfulness (FFMQ), Experiential Avoidance (BEAQ), Interoceptive Awareness (MAIA), and Self‐Compassion (SCS‐SF) scales. We estimated changes over time using mixed models. Participants completed qualitative interviews at 4 and 24 weeks. Results: Positive urine toxicology decreased over time for cocaine ( β = −.266, p = .008) and benzodiazepines ( β = −.208, p = .028). M‐ROCC reduced PROMIS‐Pain ( Z = −2.29; p = .022), BEAQ ( Z = −2.83; p = .0005), and increased FFMQ ( Z = 3.51; p < .001), MAIA ( Z = 3.40; p = .001), and SCS‐SF ( Z = 2.29; p = .022). Participants with co‐morbid anxiety had decreased PROMIS‐Anxiety ( Z = −2.53; p = .012). Interviewed participants commonly used mindfulness practices for stress and anxiety (12/12, 100%), and to reduce pain catastrophizing and rumination (7/12, 58%). Conclusion and Scientific Significance: This is the first study to report the effects of a 24‐week mindfulness program during buprenorphine treatment on common comorbidities, including pain interference, anxiety, cocaine, and benzodiazepine use. The findings that M‐ROCC is associated with reduced experiential avoidance, as well as increased interoceptive awareness and self‐compassion, align with proposed mechanisms that are now extended to OUD treatment. Future larger randomized controlled trials are needed before effectiveness can be established and the role of these mechanisms can be confirmed.